(untitled) (Palíndromo, 2014)
The essay consists of four letters exchanged between the authors; in which fantastic cities are described, looking to generate, through these descriptions, an offset to reflect on contemporary cities and their processes of expression and territorial planning. We chose an experimental writing, that seeks to bring the place of sensitive understanding and perception of the city. The letters trigger a phenomenological and from his reflections on perceptual experience and aesthetics of the city are performed theoretical framework, making the desire to fly a city that can be a fraught urban laboratory of possibilities in the constitutions of subjects.